EDUCATIONAL INSTITUTION’S USE OF SOCIAL MEDIA: A CASE STUDY FROM EDUTOPIA - Muhtar Ahmad (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2017)
This is a case study that elaborates how George Lucas Educational Foundation (GLEF), an educational institution that is broadly known as Edutopia, employes social media to advocate their learning strategies. Social media usage decision is determined by the strategic goals that organizations want to accomplish. Organizations should decide, whether they need to pick from existing social media platforms, to establish their own applications, or to use both. In this regards, Edutopia uses both its own-developed and existing social media platforms. Therefore, this study is aimed to: 1) elaborate the relevant advantages of each type of those platforms to its mission, 2) to study opportunities that Edutopia has to build relationship with its users though its forum and blogs, and 3) to analyze the functions of social media to understand the appropriateness of using different social media platforms. The data were collected using interview, observation, and documenting from April until June, 2014 and were analyzed using pattern matching logic. The results showes that both own-developed and existing platforms are beneficial for Edutopia as they seem to have different characteristics, target users, as well as different level of engagement. The study also showes that Edutopia’s user engagement level was significantly high which meant Edutopia has been using their various social media channel to effectively build its community. Finally, Edutopia has functionally utilizes its social media to bring its mission to: 1) document , 2) disseminate, and 3) advocate its learning solutions to teachers, parents, administrators, education leaders, and other stakeholders.Keywords: social media, community building.